The Effectiveness of Video- Based Lactation Education on Breastfeeding Confidence in Postpartum Mothers - Dewi Parwati; Armiyati Nur; Susanti Susanti; Rezqiqah Aulia Rahmat; Ni Luh Gede Sri Wahyudianti (International Journal of Health Sciences, 2026)
ABSTRACT A mother's confidence in breastfeeding is a crucial factor influencing successful breastfeeding. Lack of knowledge and experience in breastfeeding often leads to postpartum mothers feeling insecure about breastfeeding their babies. Video-based lactation education is an effective educational method because it delivers information visually and audibly in an engaging manner. This study aims to analyze the effectiveness of video-based lactation education on increasing breastfeeding confidence in postpartum mothers. The study used a quasi-experimental design with a pretest - posttest approach. The study sample consisted of 50 postpartum mothers selected using a purposive sampling technique. Data were collected using a breastfeeding questionnaire. Self-Efficacy Scale (BSES). Data analysis used paired t- test. The results showed that the average breastfeeding confidence score increased from 48.6 ± 7.5 to 67.8 ± 6.9 after video-based lactation education (p < 0.001). It was concluded that video-based lactation education was effective in increasing postpartum mothers' confidence in breastfeeding. Keywords: Lactation Education, Educational Videos, Breastfeeding Confidence, Postpartum Mothers